Ethnobotanical uses of plants by Brangkuah Community of Moyo Island, West Nusa Tenggara, Indonesia: Ethnobotanical use of plants in Indonesia (Journal of the Bangladesh Agricultural University, 2019)
An ethnobotanical study at Moyo Island, West Nusa Tenggara was carried out to record the traditional knowledge and utilization of plant species there. It is expected that traditional knowledge can play a role in natural resource management systems which can be used in conservation programs. This research was conducted with field observational methods in the Moyo forest and interviews with local people that have knowledge about utilization of plants. There are about 48 species of plants which are utilized by the Brangkuah Community in  Moyo Island. Most of them are collected from the forest and 21% (10 species) are cultivated. Local people also use plants for medicine 41% (21 species), food 39% (20 species) and building materials 16%  (8 species). The Brangkuah have started to cultivate several plants which are used as building material and food plants which previously collected from the forest. The Brangkuah community has conserved useful plants for their daily life. It is expected that the forest is sustainable.J Bangladesh Agril Univ 17(3): 325–337, 2019